K.D.Ushynskyi about the Correlation of Education and Training in Various European Schools - Korneiko, Yuliia (Pedagogical Discourse, 2017)
The article analyzes the pedagogical heritage of the outstanding national pedagogical scientist K. Ushynskyi and his progressive ideas on the problem of the unity of the tasks of education and upbringing in various European schools. Study of the peculiarities of K.D. Ushynskyi’s pedagogical activity made it clear that his research of pedagogical theories and educational systems in Europe and America played the role of an active catalyst in the formation of a scientist’s pedagogical outlook. And also, he created the groundwork, which then formed his own pedagogical concept. The synthetic way of the scientist thinking, his desire for philosophical comprehension of the pedagogical process ensured the success necessary for the beginner-researcher in the process of preparatory work. This allowed K.D. Ushynskyi not to confine himself to a narrow branch or a direction of pedagogical thought, as most of his contemporaries, not to focus on finding just common and different in these directions, but to study their origins, mechanisms of formation, etc. This is what formed a new approach to the study of pedagogical phenomena, identified new techniques and methods for their explanation. The results of his critical review of the ways of combining administrative, training and educational elements in European schools are summarized. K.Ushynskyi gave the recommendations of concerning the reform of the school system in the national system of education. First of all, hе saw the reforming of the national education in the creation conditions for the formation of behavioral experience as the basis of the spiritual and moral formation of the individual. He emphasized on the complex and active nature of the educational interaction between a teacher and a student, the functioning of the school as a community, where civil, social education is a component of general education. It is shown how ideas, persuasion of the well-known teacher, comparative scientist K.Ushynskyi in modern school education of Ukraine can be embodied.